A closed-loop electrical stimulation system triggered by EOG for acupuncture therapy. Issue 1 (1st January 2020) - Yuan, Ding; Li, Yurong; Wang, Tian; Chen, Jianguo; Chen, Dongyi; Lin, Dong; Yang, Yuan
Abstract : Acupuncture therapy is an often-used traditional Chinese medicine intervention of autism spectrum disorder. Acupuncture is usually delivered by therapists; thus, its effectiveness highly relies on their experience. This paper designed a closed-loop electrical stimulation treatment system triggered by neurophysiological signals, in order to improve the conventional acupuncture in clinical trials. Electrooculogram (EOG) signals are collected and analyzed synchronously while autistic children are watching the specifically designed visual evocation system. The electrical stimulation is triggered once the attention state is determined, delivering stimulation to the Changqiang acupoint (between the tailbone and the anus). Three healthy volunteers and four autistic children participated in this proof-of-concept study. Prior to the online test, the subject-special EOG template was determined offline. We obtained the mean recognition rate of 95.45% for healthy participants and 89.43% for autistic children, and the mean false recognition rate of 2.51% for healthy participants and 7.23% for autistic children by template matching algorithm. The system was able to recognize the EOG pattern of attention to the state and successfully trigger the electrical stimulation. This study is the first time to combine acupuncture and bioelectrical signal to provide an automatic closed-loop electrical stimulation system for acupuncture therapy.